2001
DOI: 10.1002/1097-0142(20010101)91:1<123::aid-cncr16>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined choriocarcinoma and adenocarcinoma of the lung occurring in a man

Abstract: BACKGROUND Human chorionic gonadotropin (hCG)‐producing large or giant cell carcinoma of the lung is not uncommon, but primary pulmonary choriocarcinoma is an extremely rare entity. Even rarer are cases occurring in males; to date the authors have found only 12 reported cases in the English literature. METHODS The clinical record of a 61‐year‐old man who presented with hemoptysis is described. A review of the literature regarding patients with primary pulmonary choriocarcinoma also is reported. RESULTS Compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 19 publications
(20 reference statements)
0
41
0
3
Order By: Relevance
“…In our case, the tumor was consisted of a choriocarcinomatous component (cytotrophoblastic and syncytiotriphoblastic cells) and poorly diffenrentiated adenocarcinoma. To our knowledge, only one case of combined choriocarcinoma and adenocarcinoma of the lung has been reported by Chen et al so far [3]. Chen et al reported that there is the possibility that choriocarcinoma and adenocarcinoma arouse simultaneously or formed a collision tumor; however, it is considered that the choriocarcinoma might occur directly in the lung through trophoblastic differentiation of some cells in the former adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the tumor was consisted of a choriocarcinomatous component (cytotrophoblastic and syncytiotriphoblastic cells) and poorly diffenrentiated adenocarcinoma. To our knowledge, only one case of combined choriocarcinoma and adenocarcinoma of the lung has been reported by Chen et al so far [3]. Chen et al reported that there is the possibility that choriocarcinoma and adenocarcinoma arouse simultaneously or formed a collision tumor; however, it is considered that the choriocarcinoma might occur directly in the lung through trophoblastic differentiation of some cells in the former adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, the finding of a coexistent somatic neoplasm in other cases of endometrial YST, principally those arising in perimenopausal and postmenopausal women, suggests that a proportion of cases arise as a result of ''neometaplasia'' or ''retrodifferentiation,'' or from malignant pluripotent somatic stem cells, as has been postulated to occur in the ovary and at extragonadal sites such as the stomach (18). There are similarities between the occurrence of a YST component in association with a somatic neoplasm and the presence of a component of choriocarcinoma in adenocarcinomas of various organs, such as the lung, breast, uterus, colon, and bladder (19)(20)(21)(22)(23). Two cases of pure endometrial YST have been reported in women of perimenopausal age and we suspect that these were somatically derived with complete overgrowth of the native tumor by the YST.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 lists 31 cases of lung carcinoma with trophoblastic differentiation, or the choriocarcinoma of the lung, retrieved from the English literature [3][4][5][6][7][8]. For 18 of the 31 cases, including duplicates, anti-cancer chemotherapy was employed using the regimens shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%